Analyzing the content of the two science books for intermediateStageaccording to NGSS standards - et. al., Prof. Dr. HaiderMasyarHamadallah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research aims to analyze the content of the two science books for the intermediateStage according to NGSS standards, and the two researchers relied in their answers to the research question on the descriptive analytical method, as the research community and its sample are partly from the content of the science books for the intermediate grade (first and second grade), in both parts, the two researchers prepared the research tool in its initial form represented by the list of dimensions of NGSS standards (scientific and engineering practices, comprehensive concepts, core ideas) after translating it into Arabic, which they obtained from the National Research Council (NRC) website, to ensure the validity of the research tool, it was presented to (24) of the arbitrators specialized in curricula, teaching methods, measurement and evaluation fields, psychology and life sciences, to know its suitability to the nature of the research. Among the most important findings of the researchers is that the interest of the two science textbooks for the intermediate Stage with science standards for the next generation was average compared to the spoken percentage to include the standards adopted by the researchers based on previous studies and the opinions of the referees.